Avaliação da biocompatibilidade e ação antimicrobiana de membranas de osso bovino impregnadas com metronidazol e clorexidina - Camargo, Jose Augusto Resende (2009)
The aim of the research was to analyze the histological behavior and the antimicrobial action of resorbable bone membrane impregnated with watery solution of metronidazol 10%, watery solution of chlorhexidine 0.12% and watery solution of chlorhexidine 2%. The tecidual reaction was analyzed using subcutaneous of Wistar rats (Rattus norvegicus) for insertion of the impregnated membranes. The analysis was carried through of descriptive form as to the inflammatory alterations (presence of edema, vascular changes and) and to the reparation processes (degree of fibrose, angioblastic and fibroblastic proliferation) found in the tissues and by means of histomorfometric test involving the membran inserted. For the evaluation of antimicrobial action, the membranes was cut in circles of 4,2 mm in diameter and immersed in antimicrobial substances during 3 minutes. The control group was immersed in saline solution. They were divided into a group immediately inserted on the agar plate and other group inserted 07 days after the impregnation. The method of choice for the evaluation of antimicrobial action of the substances in study was the diffusion of the agent in a radial manner in agar of culture. The sensitivity of microorganisms was detected by the presence or not of inhibition halos. The microorganisms used for the evaluation were Enterococcus faecalis and Pseudomonas aeruginosas. In the histological analysis the membranes impregnated with metronidazol had presented moderate inflammatory infiltrate, but little in the majority of specimens. The reaction with chlorhexidine 0.12% was generality moderate, but intense in some analyzed specimens. The tissues that surrounded the membrane impregnated with chlorhexidine 2% had demonstrated to greater presence of edema, inflammatory infiltrate more intense and lesser degree of fibrosis in all evaluation periods. In the antimicrobial tests, the results demonstrated antimicrobial action for both microorganisms tested only with the use of chlorhexidine 2%. The use of metronidazole 10% and chlorhexidine 0.12% were harmless to the two samples.